A 30 V rail-to-rail operational amplifier. Issue 10 (October 2015) - Wang, Chua-Chin; Tsai, Tsung-Yi; Lu, Wen-Je; Chen, Chih-Lin; Wu, Yi-Lun
Abstract This work presents a high-voltage (HV) operational amplifier (OPA). OPAs are widely used in signal conditioning circuits for industrial applications and integrated circuits (ICs). Particularly, in HV applications like BMS (battery management system), the signal conditioning circuits are always used to transfer voltage signal between HV domain and low voltage (LV) domain. Notably, the voltage from the HV domain could be as high as tens of volts, which might cause damages to regular silicon-based transistors. Nevertheless, since the resolution of the signal conditioning circuits depends on the output range and the operation range is determined by the input range, the input and output ranges of the signal conditioning circuits have been a key issue in the HV applications. We propose a rail-to-rail HV OPA to resolve these issues. The proposed design is implemented using <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6g4w" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.25μm</alternatives> 1-poly 3-metal 60 V BCD process. The core area is <alternatives><inline-graphic xlink:href="ark:/27927/pgj2p3q6k96" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.809×0.303mm2</alternatives>. DC gain and unit-gain bandwidth of the proposed rail-to-rail HV OPA are measured to be 41 dB and 0.3 MHz, respectively. Finally, the proposed rail-to-rail HV OPA is proven on silicon to receive any signals between 0 and 30 V and transmit a signal in the range of [0.4, 29.6] V.